Prevalence and the associated risk factors of gastrointestinal parasites of shoats in Tiyo District, Arsi zone, Oromia, South West Ethiopia - Tadalech Kabada; Dimshasha Tolera; Abaje Abera (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
A cross-sectional study was conducted during October 2018 to November 2019 in Tiyo district, Arsi Zone of Oromia National Regional State in order to determine the prevalence of Shoats GIT parasites and the associated risk factors. A total of 384 fecal samples were collected from all animals. The collected samples were kept in cold chain and transported to Asella Regional Veterinary Laboratory. The quantitative method of fecal examination was conducted by using a modified McMaster egg-counting technique. The overall prevalence of GIT parasites was 70.5% (271/384). The prevalence of GIT parasites in sheep and goats were 52.8% (150/284) and 64% (64/100) respectively. The most GIT parasites found in the study area was Strongyle (39%), Stronglyoid (21%), Trichuris(11%) Paramphistomum (74%), Monezia (6%) Coccidia (25%) and mixed infection (121%). The degree of light, medium and severe GIT infestations in the study area was, 88(22.9%), 56(14.5%) and 75(19.5%) respectively. There was no significant association of parasites infestations with district, species, age and body conditions of the animals (P>0.05). This study showed that, GIT parasites are the major health problems of small ruminants in the study area. Therefore, a further study on species of GIT parasites circulating in the area is crucial. Cost effective deworming strategy and awareness creations to the farmers in the study area should be advised.